Bilateral congenital chest wall defects associated with microtia: First case report - Ayman Alkhamisy; Atya Gb; Ghada Alyousef; Fatema Alzahraa Alseddiki; Mohamad Morjan (Elsevier, 2022)
Congenital chest wall defects are uncommon and present commonly at birth or later in infancy. The most common types are pectus excavatum, pectus carinatum, and sternal clefts. We present the first case report of multiple congenital anomalies that include bilateral chest wall defects with complete absence of the skin and muscular layer plus microtia that are associated with right facial nerve paralysis. The baby was managed conservatively with an application of a daily dressing. Both defects healed properly and closed after seven weeks of treatment without evidence of a hernia. On follow-up, after five years the boy was seen with good scars without complications.